MODEL PENYELESAIAN KREDIT BERMASALAH PADA CREDIT UNION (Studi Di Credit Union Khatulistiwa Bakti Pontianak) - FRANSISKUS SAJU, SH. A2021141008, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses a model settlement of non-performing loans in the credit union (Study In The Credit Union Equator Pontianak Bakti). The method used in this research is empirical juridical approach. From the results of this thesis research we concluded that implementation of the loan agreement at the Credit Union